Evaluation of a Probability-Based Predictive Tool on Pathologist Agreement Using Urinary Bladder as a Pilot Tissue - Jones E; Woldeyohannes S; Castillo-Alcala F; Lillie BN; Sula M-JM; Owen H; Alawneh J; Allavena R (MDPI (Basel, Switzerland), 2022)
Inter-pathologist variation is widely recognized across human and veterinary pathology and is often compounded by missing animal or clinical information on pathology submission forms. Variation in pathologist threshold levels of resident inflammatory cells in the tissue of interest can further decrease inter-pathologist agreement. This study applied a predictive modeling tool to bladder histology slides that were assessed by four pathologists: first without animal and clinical information, then with this information, and finally using the predictive tool. All three assessments were performed twice, using digital whole-slide images (WSI) and then glass slides. Results showed marked variation in pathologists' interpretation of bladder slides, with kappa agreement values of 7-37% without any animal or clinical information, 23-37% with animal signalment and history, and 31-42% when our predictive tool was applied, for digital WSI and glass slides. The concurrence of test pathologists to the reference diagnosis was 60% overall. This study provides a starting point for the use of predictive modeling in standardizing pathologist agreement in veterinary pathology. It also highlights the importance of high-quality whole-slide imaging to limit the effect of digitization on inter-pathologist agreement and the benefit of continued standardization of tissue assessment in veterinary pathology.
Keywords: bladder disease; canine; concurrence; feline; glass slides; inter-pathologist agreement; predictive modeling; veterinary pathology; whole-slide images